Intergenerational professional relationships in elementary school teams: a social network approach - Kendra Geeraerts; Piet Van den Bossche; Jan Vanhoof; Nienke Moolenaar (EARLI, 2017)
This paper examines the extent to which school team members' professional relationships are affected by being part of a certain generational cohort. These professional relationships provide opportunities for intergenerational knowledge flows and can therefore be relevant for intergenerational learning. Nowadays these topics have gained more attention due to worldwide demographic changes such as increased retirement rates and high levels of teacher dropout. Data were gathered through a survey with socio-metric questions among 299 school team members in 15 elementary schools in the Netherlands. Using social network analysis, in particular p2 modelling, we analysed the effect of being part of a generational cohort on teachers' likelihood of having professional relationships in networks such as discussing work, asking and providing advice, and collaboration. Findings indicate that generational cohorts based on chronological age do matter in the formation of work related ties. These findings also support the importance of focusing on different professional networks since different age dynamics can be at play. Our findings also show that school team members of the youngest cohort tend to form intra-generational relationships, whereas older generational cohort members prefer inter-generational relationships. This study is innovative due to its application of social network analysis to investigate intergenerational knowledge flows.